Increased Prevalence of Minor Physical Anomalies Among the Healthy First-Degree Relatives of Bipolar I Patients – Results With the Méhes Scale - Csulak, Tímea; Csábi, Györgyi; Herold, Róbert; Vörös, Viktor; Jeges, Sára; Hajnal, András; Kovács, Márton Áron; Simon, Maria; Herold, Márton; Tóth, Ákos Levente; Tényi, Tamás (Frontiers in Psychiatry, 2021)
Minor physical anomalies are somatic markers of aberrant neurodevelopment, so the higher prevalence of these signs among the relatives of bipolar I patients can confirm minor physical anomalies as intermediate phenotypes. The aim of the study was to investigate the rate and topological profile of minor physical anomalies in first-degree healthy relatives of patients with bipolar I disorder compared to matched normal control subjects. Using a list of 57 minor physical anomalies (the Méhes Scale), 20 first-degree unaffected relatives of patients with the diagnosis of bipolar I disorder and as a comparison 20 matched normal control subjects were examined. Minor physical anomalies were more common in the ear, head, mouth and trunk regions among the relatives of bipolar I patients compared to normal controls. By the differentiation of minor malformations and phenogenetic variants, we have found that both minor malformations and phenogenetic variants were more common among the relatives of bipolar I patients compared to the control group, while individual analyses showed, that one minor malformation (sole crease) and one phenogenetic variant (high arched palate) were more prevalent in the relative group. This is the first report in literature on the increased prevalence of minor physical anomalies among the first-degree unaffected relatives of bipolar I patients. The results can support the concept, that minor physical anomalies can be endophenotypic markers of bipolar I affective disorder.